Replaying the evolutionary tape to investigate subgenome dominance in allopolyploid Brassica napus - Bird, Kevin A. (John Wiley and Sons Inc., 2021)

(untitled) (New Phytol)
Allopolyploidisation merges evolutionarily distinct parental genomes (subgenomes) into a single nucleus. A frequent observation is that one subgenome is ‘dominant’ over the other subgenome, often being more highly expressed. Here, we ‘replayed the evolutionary tape’ with six isogenic resynthesised Brassica napus allopolyploid lines and investigated subgenome dominance patterns over the first 10 generations postpolyploidisation. We found that the same subgenome was consistently more dominantly expressed in all lines and generations and that >70% of biased gene pairs showed the same dominance patterns across all lines and an in silico hybrid of the parents. Gene network analyses indicated an enrichment for network interactions and several biological functions for the Brassica oleracea subgenome biased pairs, but no enrichment was identified for Brassica rapa subgenome biased pairs. Furthermore, DNA methylation differences between subgenomes mirrored the observed gene expression bias towards the dominant subgenome in all lines and generations. Many of these differences in gene expression and methylation were also found when comparing the progenitor genomes, suggesting that subgenome dominance is partly related to parental genome differences rather than just a byproduct of allopolyploidisation. These findings demonstrate that ‘replaying the evolutionary tape’ in an allopolyploid results in largely repeatable and predictable subgenome expression dominance patterns.